EVALUATION OF ANTINOCICEPTIVE AND ANTI-INFLAMMATORY EFFECT OF THE HYDROALCOHOLIC EXTRACTS OF LEAVES AND FRUIT PEEL OF P. GRANATUM IN EXPERIMENTAL ANIMALS. - J. SALWE, KARTIK; SACHDEV, DEVENDER (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Background: We investigated antinociceptive, acute and chronic anti-inflammatory activity of hydroalcoholic extracts of leaves and fruit peel of P. granatum and compared it with standard drug Ibuprofen. Materials and Methods: Hydroalcoholic extracts of leaves and fruit peel of P. granatum was prepared using Soxhlet apparatus. Swiss albino mice weighing 25 Â± 5 g and Wistar albino rats weighing 120 Â± 10 g of either sex were used in this study. The antinociceptive property of both the extracts was screened by acetic acid-induced writhing in mice while acute and chronic anti-inflammatory property was studied using the carrageenan-induced paw edema and cotton pellet induced granuloma model respectively in rats. The percent inhibition of the writhing response, paw edema and dry weight of cotton pellet induced granuloma was noted. Results: Leaves and fruit peel extracts of P. granatum exhibited a significant reduction in writhing, carrageenan induced paw edema and weight of cotton pellet induced granuloma when compared to control. Fruit Peel extract of P. granatum at higher dose was found better than leaves extract of P. granatum at higher dose. Antinociceptive and acute and chronic anti-inflammatory activity of the standard drug Ibuprofen treatment was better than all the extracts, but there was no significant difference between the activities at higher doses of both plant extracts and standard drug. No toxicity was observed even when both extracts were administered at 10 times of highest dose used in this study. Conclusion: The results obtained indicate that fruit peel and leaves of P. granatum has favorable analgesic and anti-inflammatory activities and thus support the traditional use of fruit peel and leaves of Â P. granatum as analgesic and anti-inflammatory agent. Key words: Antinociceptive, Anti-inflammatory, Acetic acid, Carrageenan, Cotton pellet, Punica granatum.